The Influence of Kahoot!-Basedé—ªå˜å¡shÇŽncÃºn KÇŽ Media on The Use ofè¿˜æ˜¯hÃ¡ishÃ¬ And æˆ–è€…huÃ²zhÄ› in Constructing Mandarin Sentences at College Student Level - Nadzifah, Hidayatun; Suyatno, Suyatno; Amri, Miftachul; Laily, Ulul (UNDIKMA, 2025)
Technological advances in education have provided enormous benefits for educators and students to access information more widely and effectively. It proves that technology encourages the development of a more interactive and interesting educational approach. With the existence of learning media, students will be stimulated to think, feel, have interests and attention through messages conveyed on the media used in learning. This study uses Kahoot!-based é—ªå˜å¡ShÇŽncÃºn kÇŽ media in constructing Mandarin sentences. The purpose of this study is to identify the influence of Kahoot!-based é—ªå˜å¡ShÇŽncÃºn kÇŽ media on the use of è¿˜æ˜¯hÃ¡ishÃ¬ and æˆ–è€…huÃ²zhÄ› in constructing Mandarin sentences. This learning is applied to 3rd semester students of the Polytechnic, University of Surabaya, Accounting Study Program and Marketing Management Study Program. This study uses a qualitative descriptive approach. The data sources for this study are observations, interviews, documents, and questionnaires on Google Form. The results of this study indicate that learning using Kahoot!-based é—ªå˜å¡ShÇŽncÃºn kÇŽ media is very effective and makes it easier for students to understand the mastery of constructing Mandarin sentences.